Changes in myocardial cytoskeletal intermediate filaments and myocyte contractile dysfunction in dilated cardiomyopathy: an in vivo study in humans. Issue 6 (1st December 2000) - Di Somma, S; Marotta, M; Salvatore, G; Cudemo, G; Cuda, G; De Vivo, F; Di Benedetto, M P; Ciaramella, F; Caputo, G; de Divitiis, O
Abstract : AIM: To investigate in vivo the intermediate cytoskeletal filaments desmin and vimentin in myocardial tissues from patients with dilated cardiomyopathy, and to determine whether alterations in these proteins are associated with impaired contractility. METHODS: Endomyocardial biopsies were performed in 12 patients with dilated cardiomyopathy and in 12 controls (six women with breast cancer before anthracycline chemotherapy and six male donors for heart transplantation). Biopsy specimens were analysed by light microscopy and immunochemistry (desmin, vimentin). Myocyte contractile protein function was evaluated by the actin-myosin in vitro motility assay. Left ventricular ejection fraction was assessed by echocardiography and radionuclide ventriculography. RESULTS: Patients with dilated cardiomyopathy had a greater cardiomyocyte diameter than controls (p < 0.01). The increase in cell size was associated with a reduction in contractile function, as assessed by actin-myosin motility ( r = −0.643; p < 0.01). Quantitative immunochemistry showed increased desmin and vimentin contents (p < 0.01), and the desmin distribution was disturbed in cardiomyopathy. There was a linear relation between desmin distribution and actin-myosin sliding in vitro ( r = 0.853; p < 0.01) and an inverse correlation between desmin content and ejection fraction ( r = −0.773; p < 0.02). Negative correlations were also found between myocardial vimentin content and the actin-myosin sliding rate ( r = −0.74; p < 0.02) and left ventricular ejection fraction ( r = −0.68; p < 0.01). CONCLUSIONS: Compared with normal individuals, the myocardial tissue of patients with dilated cardiomyopathy shows alterations of cytoskeletal intermediate filament distribution and content associated with reduced myocyte contraction.